Safety and efficacy of transdermal fentanyl in patients with cancer pain: phase IV, Turkish oncology group trial - (:unkn) unknown (WILEY, 2007)
We have performed a prospective evaluation of the efficacy, safety and convenience of the transdermal therapeutic system - fentanyl (TTS-F) in Turkish cancer patients when it was newly available in Turkey. Ninety-nine patients with historically confirmed malignancy and pain entered the study; the mean age was 55.1 (16-58) years. The study duration was 28 days. Transdermal therapeutic system - fentanyl was used in opioid-naive or pre-treated patients. Most patients reported a decrease in pain severity. Use of rescue medication decreased from day 4 to day 28. The majority of patients rated patch convenience of use as excellent. A total of 22.2% of patients experienced adverse events that were either probably related or very likely to be related to the study drug. The majority of the adverse events mentioned were related to the digestive system. Eighteen serious adverse events were reported by 13 patients. Six events were doubtfully related, and 12 events were not related to the study drug. Four patients died during the trial. None of these deaths was attributed to the study drug. In conclusion, the trial showed that TTS-F is easily managed, effective and will help to enable the appropriate opioid administration to patients who are suffering from cancer pain in Turkey.
Keywords: transdermal fentanyl; cancer pain; opioids; MORPHINE; RELEASE